Self‐Formation CoO Nanodots Catalyst in Co(TFSI)2‐Modified Electrolyte for High Efficient Li‐O2 Batteries. Issue 40 (2nd September 2022) - Sun, Guiru; Gao, Rui; Jiao, Hailiang; Luo, Dan; Wang, Yan; Zhang, Zexu; Lu, Wei; Feng, Ming; Chen, Zhongwei
Abstract: The major challenges for Li‐O2 batteries are sluggish reaction kinetics and large overpotentials due to the cathode passivation resulting from insulative and insoluble Li2 O2 . Here, a novel nanodot (ND)‐modified electrolyte is designed by employing cobalt bis(trifluoromethylsulfonyl)imide (Co(TFSI)2 ) as an electrolyte additive. The Co(TFSI)2 additive can react with discharge intermediate LiO2 and product Li2 O2 to form CoO NDs. The generated CoO NDs are well dispersed in electrolyte, which integrates both the high catalytic activity of solid catalyst and the good wettability of soluble catalyst. Under the catalytis of CoO NDs, Li2 O2 is produced and deposits on the cathode together with them. At the recharge process, these well dispersed CoO NDs help to decompose solid Li2 O2 at a lower overpotential. The Li‐O2 cells with Co(TFSI)2 exhibit a long cycle life of 200 cycles at a current density of 200 mA g −1 under a cutoff capacity of 1000 mAh g −1, as well as a superior reversibility associated with the Li2 O2 formation and decomposition. The study is expected to broaden the range of electrolyte additives and provide a new view to developing highly dispersed NDs‐based catalysts for Li‐O2 batteries. Abstract : A CoO nanodot (ND)‐modified electrolyte is designed by employing cobalt bis(trifluoromethylsulfonyl)imide (Co(TFSI)2 ) as an electrolyte additive for Li‐O2 batteries. The highly dispersed CoO NDs integrate both the high catalytic activity of solid catalyst and the good wettability of soluble catalyst, which can make a contribution to promoting the formation and decomposition of Li2 O2, achieving a superior cyclability.